О морфологическом родстве между видами родов Abramis и Blicca (Pisces, Cyprinidae) среднего течения Днепра - Павлов, П.И.; Щербуха, А.Я. (Вестник зоологии, 1975)
By means of the E. S. Smirnov method of taxonomic analysis the morphological affinity of Abramis brama (L.) with A. sapa (P a 11.) and A. ballerus (L.) - representatives of one genus Abramis is shown to be rather smaller than that with Blicca bjoerkna (L.) — a representative of the monotypical genus Blicca. It confirms an opinion of V. A. Shutov (1969) on necessity to include B. bjoerkna into genus Abramis four species of which may be united into two subgenera on the basis of their taxonomic affinity: Abramis (Abramis brama and Blicca bjoerkna) and Ballerus (Abramis ballerus, A. sapa (Pall.).